2017
DOI: 10.1002/aelm.201600554
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Durable and Flexible Thermoelectric Films from PEDOT:PSS/PVA/Bi0.5Sb1.5Te3 Nanocomposites

Abstract: approaches to significantly enhance ZT values. One is using low-dimensional TE materials [4] such as nanowire, [5,6] nanotube, [7] nanocrystal, [8] and superlattice film [9] owing to quantum size effects, and the other is based on new phonon glasselectron crystal TE materials [10] such as skutterudites, [11] clathrates, [12] and some composites [13] due to specific components and unique structures.A large amount of previous work has been devoted to the inorganic TE materials, and Bi 2 Te 3 -based alloys have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 56 publications
(105 reference statements)
2
34
0
Order By: Relevance
“…All of these results indicated that the interfacial transport also played an important role in final thermoelectric properties of hybrids apart from the simple mixed effect. Energy filtering effect has been reported to improve the Seebeck coefficient in organic−inorganic hybrids in which interfaces form energy barriers that preferentially scattered low-energy carriers 7 , 16 , 33 . This can make the relaxation time strongly depend on energy and increase the asymmetry of carrier transport about the Fermi level, resulting in an enhanced Seebeck coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these results indicated that the interfacial transport also played an important role in final thermoelectric properties of hybrids apart from the simple mixed effect. Energy filtering effect has been reported to improve the Seebeck coefficient in organic−inorganic hybrids in which interfaces form energy barriers that preferentially scattered low-energy carriers 7 , 16 , 33 . This can make the relaxation time strongly depend on energy and increase the asymmetry of carrier transport about the Fermi level, resulting in an enhanced Seebeck coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…Highest ZT values of ~0.32 for P type and ~0.2 for N type (at room temperature) were achieved in poly(3,4-ethylenedioxythiophene) (PEDOT)/SnSe nanosheets composite films and organic molecules intercalated TiS 2 single crystals, respectively 5 , 9 , 14 . Furthermore, organic−inorganic hybrid thermoelectrics can be flexible and relatively light weight 1 , 8 , 15 , 16 . These features make them feasible to act as self-powered wearable devices by utilizing body’s heat or other heat source to generate electricity, wearable temperature sensors, and flexible solid-state coolers, which are very difficult to achieve for inorganic thermoelectric materials since they are intrinsically brittle and rigid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is plenty of room to manipulate the σ and S of the composite via tuning the inorganic/organic component ratio and optimize the TE power factor. In this context, Bi 2 Te 3 /PEDOT:PSS based inorganic–organic composites have been investigated for enhancing PF/ZT . However, in the reported studies, either the S is limited by the maximum S of PEDOT:PSS [Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In the future work, we plan to continue on the following two projects: and n-type Bi2Se3 324 and organic thermoelectric materials like PEDOT:PSS polymer 325 , and we also tried to combine the organic and inorganic materials together to utilize the flexibility of polymer while using the inorganic thermoelectric materials to enhance the thermoelectric property 325 . In the future, we plan to use electrospinning technique to process the thermoelectric polymer materials and we can also introduce inorganic nanoparticles during the processing to improve the thermoelectric response.…”
Section: Recommendation For Future Workmentioning
confidence: 99%